Missing in action: the effect of obstacle position and size on avoidance while reaching - Chapman, Craig S.; Goodale, Melvyn A. (Experimental brain research, 2008)
When reaching to objects, our hand and arm rarely collide with non-target objects, even if our workspace is cluttered. The simplicity of these actions hides what must be a relatively sophisticated obstacle avoidance system. Recent studies on patients with optic ataxia and visual form agnosia have demonstrated that obstacle avoidance is an automatic process, likely governed by the dorsal stream (Schindler et al. 2004 ; Rice et al. 2006 ). The current study sought to quantify how normal participants react to changes in the size and position of non-target objects in and around their workspace. In the first experiment, 13 right-handed subjects performed reaches to a target strip in the presence of two non-target objects, which varied in depth and horizontal configuration. We found that objects with horizontal alignments that were asymmetric about midline created systematic deviations in reach trajectory away from midline, with participants seeming to maximize the distance away from the two objects. These deviations were significantly greater for objects nearer in depth and nearly disappeared when the objects were placed beyond the target strip. Accompanying this pattern of deviation were other significant obstructing effects whereby reaches were executed more slowly when objects were close in depth and close to the participants reaching (right) hand. In the second experiment, we varied the height of the two objects, as well as the depth. Object pairs were now both tall, both short, or one-short/one-tall. We replicated the significant depth effects of the first experiment, extending the finding to include sensitivity to the size of the objects. Here the obstructing effect caused by short objects was similar to tall objects when those objects were placed at the depth of the reach target, but less than the tall objects when placed at mid-reach. Taken together, these experiments suggest that humans possess a sophisticated obstacle avoidance system that is extremely sensitive and conservative in evaluating potential obstacles and adjusting the reach accordingly.